(untitled) (Materiali di Estetica. Terza serie, 2023)
By virtue of an accidental discovery, Prussian Blue has the honor of being the first synthetic pigment created by man. His story is interlaced with the lives of chemists, philosophers, writers and with the eternal question of evil and human stupidity.